2013
DOI: 10.1039/c3ee00045a
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the hydrogen evolution reaction activity in alkaline electrolytes with the hydrogen binding energy on monometallic surfaces

Abstract: The slow reaction kinetics of the hydrogen evolution and oxidation reactions (HER/HOR) on platinum in alkaline electrolytes hinders the development of alkaline electrolysers, solar hydrogen cells and alkaline fuel cells. A fundamental understanding of the exchange current density of the HER/HOR in alkaline media is critical for the search and design of highly active electrocatalysts. By studying the HER on a series of monometallic surfaces, we demonstrate that the HER exchange current density in alkaline solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
714
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 947 publications
(787 citation statements)
references
References 29 publications
45
714
1
2
Order By: Relevance
“…Yan and co-authors [30] demonstrated that the hydrogen binding energy can also be used as a descriptor for the HER activity measured in base, where a similar volcano shaped plot was also obtained (Fig. 3c).…”
Section: Science China Materialsmentioning
confidence: 91%
“…Yan and co-authors [30] demonstrated that the hydrogen binding energy can also be used as a descriptor for the HER activity measured in base, where a similar volcano shaped plot was also obtained (Fig. 3c).…”
Section: Science China Materialsmentioning
confidence: 91%
“…The lower limit was chosen to be 0.07 V to avoid the diffusion of H atom into the Pd lattice. 11 In 0.1 M KOH, the underpotential deposited hydrogen (H upd ) adsorption and desorption peaks in the potential region of 0.07-0.45 V are very asymmetric and the double layer regions are not well defined (Figure 3a), making it difficult to determine sur- face areas using the H upd adsorption and desorption peaks. Additionally, the H upd desorption peaks for all the samples in 0.1 M KOH are located at around 0.35 V (Figure 3a).…”
Section: Resultsmentioning
confidence: 99%
“…Pd and Pd-based catalysts have been studied as HOR catalysts in fuel cells, 9,10 and lower HOR/HER activities were observed on Pd/C than bulk Pd, [11][12][13] suggesting a particle size effect. However, a fundamental understanding of HOR/HER kinetics on Pd and a systematic study of the particle size effect are largely missing.…”
mentioning
confidence: 99%
“…By comparing the amount of electrons passed during the oxidation process, the relative surface areas between different Ag electrodes can be obtained (Supplementary Fig. 8) 33,39 .…”
Section: Electrochemical Characterizations and Product Analysis A Prmentioning
confidence: 99%